2019
DOI: 10.1111/dom.13936
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of insulin glargine 300 U/mL versus insulin glargine 100 U/mL in Asia Pacific insulin‐naïve people with type 2 diabetes: The EDITION AP randomized controlled trial

Abstract: Aim To compare the efficacy and safety of Gla‐300 versus Gla‐100 in insulin‐naïve people with type 2 diabetes in Asia Pacific. Materials and Methods In this open‐label, randomized, active‐controlled, 26‐week study, insulin‐naïve participants with type 2 diabetes inadequately controlled with non‐insulin antihyperglycaemic drugs were randomized (2:1) to Gla‐300 or Gla‐100. The initial daily dose of basal insulin was 0.2 U/kg and was adjusted at least weekly for 8–12 weeks to a target fasting self‐monitored plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(68 citation statements)
references
References 30 publications
4
64
0
Order By: Relevance
“…As expected, Gla-300 was associated with lower rates of hypoglycemia compared with NPH insulin. Our findings are consistent with previous results in the EDITION trials in T2D patients where Gla-300 consistently reduced nocturnal hypoglycemia compared with Gla-100 with no differences in HbA1c [ 2 , 3 ]. With comparable HbA1c and FPG achieved between treatment groups, there were notable differences in GV and TIR between the Gla-300 and NPH groups that varied by time of day.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As expected, Gla-300 was associated with lower rates of hypoglycemia compared with NPH insulin. Our findings are consistent with previous results in the EDITION trials in T2D patients where Gla-300 consistently reduced nocturnal hypoglycemia compared with Gla-100 with no differences in HbA1c [ 2 , 3 ]. With comparable HbA1c and FPG achieved between treatment groups, there were notable differences in GV and TIR between the Gla-300 and NPH groups that varied by time of day.…”
Section: Discussionsupporting
confidence: 92%
“…In the NPH group, up-titration of insulin was frequently limited by hypoglycemia. The overall basal insulin requirements were lower in this trial compared with Caucasians and could be linked to ethnic differences, as has been observed in lower dose requirements in phase 3 trials of Gla-300 in Asians in a physician-titrated setting [ 3 ]. Due to ethnic differences in basal insulin requirements, our self-titration regime was designed to be less aggressive, titrating by 1 IU weekly compared with other studies where insulin was titrated every few days [ 6 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our outcomes data are generally in line with those from the EDITION series of RCTs comparing Gla-300 and Gla-100. In the EDITION T2D studies, Gla-300 and Gla-100 were found to achieve similar glycemic control, but Gla-300 was associated with improvements in some hypoglycemia end points in insulin-experienced patients treated with basal-bolus therapy [ 5 ] or oral + basal therapy [ 6 , 7 ] and in insulin-naïve patients [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A second-generation basal insulin analog (BIA), insulin glargine 300 U/ml (Gla-300), has been associated with significant reductions in some hypoglycemia outcomes (and comparable improvements in glycemic control) in randomized controlled trials (RCTs) in patients with T2D vs. the first-generation BIA, insulin glargine 100 U/ml (Gla-100) [ 5 9 ], which has been confirmed in recent trial-level [ 10 ] and patient-level [ 11 , 12 ] meta-analyses. This advantage is likely due to Gla-300’s improved pharmacokinetic/pharmacodynamic (PK/PD) profile, longer half-life, and more stable bioavailability [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%